Uma proposta de círculo de leitura no ensino fundamental - Lima, Aline Giseli da Silva (2016)
The present work has as main objective to encourage the liking for reading in students of the 9th grade of elementary school in a public school. Believing how powerful the reading can be to transform the youths and their lives, we aim to expand the reading repertoire of these students, making them gain the habit of reading, which can last for a whole lifetime. This proposal to work with reading aims to encourage the habit of reading and also guide the learners about the work to be read, training them to be 'readers students', working on the peculiarities of the literary text, among other specific objectives. Thus, we attempt awaken the critical ability to read texts, conscious how literature acts as an agent that broadens the worldwild view and humanizes the individual, as well as being a right guaranteed to everyone. To develop our research, we resort Solé (1998), about the reading and reading strategies; to the National Curricular Parameters (1998), one of the official teaching documents, about what is expected of literature teaching. About what concerns to the formation of the reader, we resort to Bordini and Aguiar (1993). As for what specifically refers to literature, as well as reading the literary text, we resort to Jouve (2012). To reflect on the teaching of literature and textbooks, we refer to Pinheiro (2006). We still refer to Colomer (2007), concerning the importance of sharing reading. We also take the studies of Cosson (2012, 2014) to reflect on literary literacy and elaborate the proposal of formation of the reading circle. With this work, we expect to present an orientation for other educators to consider these aspects and act looking for the formation of new readers.